Pengembangan mikroskop online interaktif pada materi biologi sel guna revitalisasi pembelajaran praktikum daring - Zahra Firdaus; Jasmine Nurul Izza; Alby Aruna; Moch. Dicky Novaldi; Deny Setiawan (JINoP (Jurnal Inovasi Pembelajaran), 2022)
The COVID-19 pandemic has caused the implementation of education in Indonesia to be carried out online. Some lessons that require practice, such as Biology, experience obstacles. The solution that has been carried out is by conducting independent experiments, but this cannot facilitate practicum on submicroscopic materials such as cells. The availibility of a virtual laboratory during a pandemic that is effective, efficient, and economical is urgently needed. The purpose of this study was to produce an interactive online microscope, test the validity of the media, and test the effectiveness of the media. The research was conducted at SMA Negeri 3 Malang in grade 11 D3. This online microscope was developed by Lee and Owens (2004) including Analyze, Design, Development, Implementation, Evaluation. The Analyze stage produced need assessment and front-end analyze data. The Design stage produced material and media designs. The Development stage produced an interactive online microscope with a material validation value of 93%, media validation 88%, and a practicality test of 96%. The Implementation phase was not carried out. In Evaluation stage, an evaluation is carried out for media evaluation. It can be concluded that this online microscope is practical and valid to meet the needs of online practicum